Longitudinal study of the effect of pregnancy on maternal and fetal cobalamin status in healthy women and their offspring. - MOLLOY, ANNE MARIE (My University, 2007)
Compromised cobalamin status during pregnancy may put both mother and child at risk of deficiency during lactation and subsequent development. We investigated whether changes in cobalamin status during pregnancy are associated with impaired status in the mother and the cord. Plasma cobalamin, methylmalonic acid (MMA), and holotranscobalamin (holoTC) concentrations were determined in 92 women at preconception, 8, 20, and 32 wk of pregnancy, at labor, and in the cord. All variables [geometric mean percentiles 10, 90 (P10, P90)] were significantly reduced from preconception [cobalamin: 293 (155, 535) pmol/L; holoTC: 63 (38,98) pmol/L; MMA: 0.12 (0.09, 0.17) ?mol/L] by 20 wk of pregnancy [cobalamin: 230 (123, 432) pmol/L; holoTC: 48 (34,78) pmol/L; MMA: 0.11 (0.08, 0.15) ?mol/L P < 0.001]. Plasma cobalamin and holoTC remained lower throughout the remainder of pregnancy [32 wk: 198 (107, 339); labor: 224 (117, 444); P < 0.001] and [32 wk: 45 (26,82); labor: 40 (23,79); P < 0.05], respectively. By 32 wk, MMA was greater than preconception [0.14 (0.09, 0.20) ?mol/L; P < 0.01]. Plasma holoTC at 32 wk and at labor was negatively correlated with cord MMA (r = ?0.51, P < 0.001 and r = ?0.40, P < 0.01, respectively). Women with lower holoTC at preconception had greater increases in MMA at 32 wk and at labor. Maternal MMA at 32 wk and at labor was significantly and independently associated with cord MMA only in women with lower holoTC at preconception (regression models: R2 = 0.707, 0.682, respectively; P < 0.01). The moderate increases observed in the cobalamin biomarker, MMA, during pregnancy may indicate a functional depletion in intracellular cobalamin status.
PUBLISHED
PubMed ID: 17634256
Keywords: Clinical Medicine